Simultaneous Determination of Major Molnupiravir Metabolite (β-D-N4-hydroxycytidine) and Favipiravir in Human Plasma by HPLC-MS/MS - T. N. Komarov; P. K. Karnakova; O. A. Archakova; D. S. Shchelgacheva; N. S. Bagaeva; I. E. Shohin; K. Ya. Zaslavskaya; P. A. Bely (Разработка и регистрация лекарственных средств)
Introduction. Coronavirus disease 2019 (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus (severe acute respiratory syndrome-related coronavirus 2). COVID-19 is now expected to stay with us for many years as a recurring disease. Molnupiravir and favipiravir are oral antiviral drugs with anti-RNA polymerase activity. The Russian Health Ministry has approved molnupiravir and favipiravir for the treatment of COVID-19. The study describes development and validation of high-performance liquid chromatography – tandem mass spectrometry (HPLC-MS/MS) method for the simultaneous determination of β-D-N4-Hydroxycytidine and favipiravir in human blood plasma. The method could be applied in pharmacokinetic study of molnupiravir and favipiravir.Aim. The aim of this study is to develop and validate a HPLC-MS/MS bioanalytical method for the determination of β-D-N4-Hydroxycytidine and favipiravir in human plasma.Materials and methods. The determination of β-D-N4-Hydroxycytidine and favipiravir in human plasma by HPLC-MS/MS. The samples were processed by 0.1 % formic acid in acetonitrile. Internal standard: promethazine. Mobile phase: 0.01 mol/L Ammonium formate buffer solution (Eluent A), 0.1 % formic acid and 0.08 % aqueous ammonia in water/acetonitrile 10 : 90 (Eluent B). Column: Shim-pack GWS C18, 150 × 4.6 mm, 5 μm. Analytical range: 50.00–10000.00 ng/mL for β-D-N4-Hydroxycytidine, 250.00–20000.00 ng/mL for favipiravir in human plasma. Ionization source: electrospray ionization. Detection conditions: 260.00 m/z → 82.10 m/z, 260.00 m/z → 111.00 m/z, 260.00 m/z → 127.95 m/z (β-D-N4-Hydroxycytidine); 156.15 m/z → 65.95 m/z, 156.15 m/z → 85.00 m/z, 156.15 m/z → 113.10 m/z (favipiravir); 285.05 m/z → 198.05 m/z (promethazine).Results and discussion. This method was validated by selectivity, suitability of reference standard, matrix effect, calibration curve, accuracy, precision, spike recovery, the lower limit of quantification, carry-over effect and stability.Conclusion. The HPLC-MS/MS method for quantitative determination of β-D-N4-Hydroxycytidine and favipiravir in human plasma was developed and validated. The analytical range was 50.00–10000.00 ng/mL for β-D-N4-Hydroxycytidine, 250.00–20000.00 ng/mL for favipiravir in human plasma. This method was applied to investigate the pharmacokinetics of molnupiravir and favipiravir.